2016
DOI: 10.1007/s00011-016-0948-8
|View full text |Cite
|
Sign up to set email alerts
|

High glucose induced-macrophage activation through TGF-β-activated kinase 1 signaling pathway

Abstract: Our findings suggested that high glucose activated macrophages mainly in TAK1/MAPKs and TAK1/NF-κB-dependent manners, which lead to the polarization of macrophages towards a pro-inflammatory phenotype, and finally lead to diabetic nephropathy. In sum, the study raises novel data about the molecular mechanisms involved in the high glucose-mediated inflammatory response in macrophages.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
13
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 23 publications
(13 citation statements)
references
References 31 publications
0
13
0
Order By: Relevance
“…NF-κB is a recognized downstream signaling target molecule of TAB1/TAK1. After Toll-like receptor signal transduction, TAK1/TAB1 mediates NF-κB p65 nuclear entry through IKKα/β, inducing further inflammation [9]. Emerging evidence points to NF-κB control over the HIF signaling pathway and interaction between the HIF signaling pathway and the NF-κB signaling cascade [14].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…NF-κB is a recognized downstream signaling target molecule of TAB1/TAK1. After Toll-like receptor signal transduction, TAK1/TAB1 mediates NF-κB p65 nuclear entry through IKKα/β, inducing further inflammation [9]. Emerging evidence points to NF-κB control over the HIF signaling pathway and interaction between the HIF signaling pathway and the NF-κB signaling cascade [14].…”
Section: Discussionmentioning
confidence: 99%
“…Transforming growth factor β-activated kinase 1-binding protein 1 (TAB1) is a specific protein that interacts with transforming growth factor β-activated kinase 1 (TAK1). TAB1/TAK1 can activate nuclear factor κB (NF-κB) in high glucose (HG)-induced BMMs, regulating macrophage activation [8][9][10][11][12]. Studies suggest that activation of the NF-κB signaling pathway upregulates HIF-1α activity and enhances glycolytic metabolism in an autonomous fashion, HIF-1α may be considered as a novel therapeutic target for DN [13][14][15][16].…”
Section: Introductionmentioning
confidence: 99%
“…The early pathological changes of DN are mainly glomerulosclerosis, renal arteriolar damage, and renal tubular degeneration; interstitial fibrosis is a prominent presentation in the late stage [22]. In this study, a type 1 diabetes mellitus mouse model was established through intraperitoneal injection of Journal of Diabetes Research STZ.…”
Section: Discussionmentioning
confidence: 99%
“…Studies have found that ROS, TGF-β1and NF-κBp65 are closely associated with the etiology of bronchopulmonary dysplasia. Reactive oxygen species (ROS) which are involved in the NF-κBp65 pathway, activate S6 kinase, induce phosphorylation of IκB, and dissociate NF-κBp65, thereby causing nuclear translocation and regulation of the transcriptions of TGF-β1and other factors [3]. It has been suggested that ROS may play crucial roles in lung tissue damage [4].…”
Section: Bronchopulmonarymentioning
confidence: 99%